Readying Health Services for Climate Change: A Policy Framework for Regional Development - Bell, Erica (American Public Health Association, 2011)
Climate change presents the biggest threat to human health in the 21st century. However, many public health leaders feel ill equipped to face the challenges of climate change and have been unable to make climate change a priority in service development. I explore how to achieve a regionally responsive whole-of-systems approach to climate change in the key operational areas of a health service: service governance and culture, service delivery, workforce development, asset management, and financing. The relative neglect of implementation science means that policymakers need to be proactive about sourcing and developing models and processes to make health services ready for climate change. Health research funding agencies should urgently prioritize applied, regionally responsive health services research for a future of climate change.